Apprendre à coopérer : un défi pour l'adhésion des agriculteurs au Plan Maroc Vert - Chloe Vitry; Abdellaoui El Hassane; Patric Dugue; Eduardo Chia (2015)
Cooperation between agricultural stakeholders is an issue which stimulates lots of research. To modernize Moroccan agriculture, the Moroccan government has launched a ten-year programme: the Plan Maroc Vert (PMV), which encourages the creation of farmers’ cooperatives or associations. The first PMV results indicate that farmers are reluctant to cooperate. The goal of this paper was to explore the ability of farmers to cooperate: what conditions are needed to develop cooperation? We mainly focused on organizational learning and conducted a series of semi-structured interviews with farmers, cooperative workers and development agents in and around Sebâa Ayoune, near Meknès. We investigated the obstacles to cooperation and the factors affecting the long-term sustainability of cooperatives, identifying eight types of cooperative learning. We built an analytical framework that can be used to identify possible levers of action to enhance cooperation conditions, in particular under the PMV.